GREEN CHEMISTRY-BASED EXPERIMENTS AS THE IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT VALUES - Paristiowati, Maria; Zulmanelis, Zulmanelis; Nurhadi, Muhamad Fazar (JTK (Jurnal Tadris Kimiya), 2019)
The development of a chemistry experiment based on green chemistry aims to train and familiarize students to save on the use of chemicals, replace them with safer materials and minimize waste generated from experimental activities. Research and development methods are used to develop experimental modules based on green chemistry. The stages of research and development consist of needs analysis, product development, and product testing. The developed experiment module, implements three principles of green chemistry, i.e. preventing waste, safer chemical planning and safe use of solvents. The feasibility test by expert judgement on the material and media obtained scores 91.9% and 94.7% respectively. The results of the trials in small groups and large groups showed that the developed module was feasible to use. Student perceptions after using the module show positive results. The conclusions from the results of the feasibility test and the trial conducted indicate that the green chemistry-based kinetics' module has good criteria and in accordance with the wishes and needs of students. In addition, the implementation of this module in the kinetics experiment succeeded in making students understand and apply the principles of green chemistry. As many as 90% of students realize that there is a relationship between the application of the principles of green chemistry and the educational paradigm for sustainable development. The use of kinetics' module based on green chemistry also saved the cost of experiment material requirements by 75% per year.